ANALISIS EFISIENSI PRODUKSI KELAPA SAWIT DI PT. KARYA TANAH SUBUR : STUDI KASUS DI AFDELING I, KABUPATEN ACEH BARAT - Fitri Adiyani; Agustiar Agustiar (Universitas Serambi Mekkah, 2022)
This study aims to determine the analysis of the efficiency of palm oil production factors in Afdeling I at PT. Karya Tanah Subur, Kaway District xvi West Aceh Regency. The method of data collection in this research is to use primary data and secondary data. This research was conducted at JL. Gempong-Tutut, Padang Sikabu Village, Kaway XVI District, Aceh Regency. The research location was carried out at PT. Karya Tanah Subur in Afdeling I starting in February 2022 until May 2022. Data were analyzed using production analysis with this research being quantitative as well as survey through interviews and using surposive sampling technique. The results of this study show that oil palm production in Afdeling I is 261.130 per month while the total production of palm oil in 2022 is 350,428 per month.